2015
DOI: 10.3399/bjgp15x683569
|View full text |Cite
|
Sign up to set email alerts
|

International variation in GP treatment strategies for subclinical hypothyroidism in older adults: a case-based survey

Abstract: BackgroundThere is limited evidence about the impact of treatment for subclinical hypothyroidism, especially among older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…vitality status, and serum TSH) all affected the decision to prescribe LT4 (33). In further analyses, the study authors found that country, TSH value of case, physician characteristic (sex and years of experience), time since the physician last diagnosed hypothyroidism in their own practice, and age of the physician's patient population all influenced LT4 prescribing.…”
Section: Combination Therapy and Physician Characteristicsmentioning
confidence: 87%
See 1 more Smart Citation
“…vitality status, and serum TSH) all affected the decision to prescribe LT4 (33). In further analyses, the study authors found that country, TSH value of case, physician characteristic (sex and years of experience), time since the physician last diagnosed hypothyroidism in their own practice, and age of the physician's patient population all influenced LT4 prescribing.…”
Section: Combination Therapy and Physician Characteristicsmentioning
confidence: 87%
“…The survey focused on patients with overt hypothyroidism, and respondents were members of a specialty society. In contrast, a survey of general practitioners from Europe and New Zealand conducted in approximately 2014 examined LT4 prescribing patterns for treatment of subclinical hypothyroidism (32,33). The country the prescribing physician was from and several characteristics of the patient case (age, Controlling for all physician characteristics (number of years in practice, country of practice, and specialty).…”
Section: Discussionmentioning
confidence: 99%
“…8 The lack of evidence for older patients may have contributed to significant treatment variation by primary care clinicians. 9 This study combined data from the Institute for Evidence-Based Medicine in Old Age (IEMO) 80-plus thyroid trial 10 and the subgroup of participants in the Thyroid Hormone Replacement for Untreated Older Adults With Subclinical Hypothyroidism Trial (TRUST) aged 80 years and older. 5 The 2 trials examined the effects of managing subclinical hypothyroidism with levothyroxine on quality of life in adults aged 80 years and older.…”
mentioning
confidence: 99%
“…[14] In most adult patients, an average dose of 1.6 mcg/kg/day is required. The initial dose may be 1 mcg/kg/day in healthy patients or a fixed dose of 12.5–25 mcg in patients at risk of heart failure.…”
Section: Dose Of Levothyroxinementioning
confidence: 99%